2008
DOI: 10.1002/ase.44
|View full text |Cite
|
Sign up to set email alerts
|

Peer teaching among physical therapy students during human gross anatomy: Perceptions of peer teachers and students

Abstract: Despite nearly 200 accredited entry-level physical therapist education programs in the United States that culminate in a doctoral degree, only a paucity of reports have been published regarding the efficacy of peer teaching in gross anatomy. No one has described the usefulness of peer teaching from the viewpoint of the peer teacher. An organized peer teaching method provided by four second-year doctors of physical therapy (DPT) students in a semester course in gross anatomy had a positive impact on the academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 15 publications
6
76
1
Order By: Relevance
“…Students reported that peer teaching helped in their development of communication skills, self-reflection, and time management which is consistent with the findings of Youdas et al [6]; Evans & Cuffe [11]; McKenna & French [7]. It is the attainment of these professional behaviors that are essential for all professionals but are often difficult to develop in the traditional classroom environment [16].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Students reported that peer teaching helped in their development of communication skills, self-reflection, and time management which is consistent with the findings of Youdas et al [6]; Evans & Cuffe [11]; McKenna & French [7]. It is the attainment of these professional behaviors that are essential for all professionals but are often difficult to develop in the traditional classroom environment [16].…”
Section: Discussionsupporting
confidence: 81%
“…It is a teaching exchange whereby students of similar backgrounds, separated by one to two years, teach each other [4]. Originally adopted by medical schools throughout the world, peer teaching has been found to be very successful when applied to other health professions including nursing and physical therapy [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Peer teaching has been used in a variety of guises including peer-assisted learning, team-based learning (TBL) and reciprocal peer teaching, and in many different areas of health education and the biosciences (Krych et al, 2005;Tariq, 2005;Gill et al, 2006;Secomb, 2007;Evans and Canavan, 2008;Shankar and Roopa, 2009). Within anatomy, peer teaching has been widely recognized as a valuable approach for learning and has been effectively incorporated into medical, dental, and healthcare curricula (Nnodim, 1997;Brueckner and MacPherson, 2004;Youdas et al, 2008). The manner of peer teaching has varied extensively and has included one-toone teacher-tutee interactions, group peer teaching, problembased learning, or even peer-developed learning materials (Walker-Bartnick et al, 1984;Lake, 1999;Krych et al, 2005;Nieder et al, 2005;Youdas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Within anatomy, peer teaching has been widely recognized as a valuable approach for learning and has been effectively incorporated into medical, dental, and healthcare curricula (Nnodim, 1997;Brueckner and MacPherson, 2004;Youdas et al, 2008). The manner of peer teaching has varied extensively and has included one-toone teacher-tutee interactions, group peer teaching, problembased learning, or even peer-developed learning materials (Walker-Bartnick et al, 1984;Lake, 1999;Krych et al, 2005;Nieder et al, 2005;Youdas et al, 2008). While many of these examples have involved students in the same year of training or in immediately adjacent years and therefore meet the definition of peer teaching, other activities which include alternate forms of tutor-led teaching where direct peers are not involved have also been regarded as peer teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Trainers have been established as an effective teaching resource in several areas of gross anatomy education. [19][20][21] This study gave also the opportunity for 'stepped procedure' learning in surgical education. First residents see the anatomical structure in real body but bloodless and safely.…”
Section: Discussionmentioning
confidence: 98%